Light of images - Baharuddin, Nasir; Salehuddin, Adam; Abdul Shukor, Shureen Faris; Abu Bakar, Shamsul (Universiti Putra Malaysia Press, 2015)
Currently, the technology of holography serves as a perfect three-dimensional medium where designers could apply innovatively to convey meanings during image-making process. The public are getting familiar and fascinated with the medium’s particular properties and characteristics of an object; they directed their attention more insistently to the pictorial independence of light, whose precise control gave them completely new opportunities to image creation and engagement.